The Challenges Facing Industries in the Peripheral Areas of Baghdad Governorate and Ways to Address Them - Farhan, Alaa; Redha , Intisar (Al-Adab Journal, 2025)
In the marginal areas of Baghdad Governorate, industries face many challenges that hinder their growth and expansion, posing obstacles to their diversity and increased productivity, as well as their localization. These problems are manifested in (raw materials, capital, workforce, marketing, transportation methods, pollution), which have a direct and indirect impact on industries. The difficulty in accessing capital affects the availability of local and imported raw materials. Capital is also an unstable and worrying factor, linked to the stability of the economic, security, and political situation. Additionally, the workforce is characterized by instability in its work in the private sector, with some workers turning to government jobs due to the lack of future guarantees in the private sector. Most industrial establishments do not rely on daily production schedules but depend on consumer demand, leading to fluctuating and unstable work in industrial establishments, resembling a form of disguised unemployment in the industrial sector. Consequently, some workers have shifted to work in government industrial establishments, which have also become bloated with employees since 2003, A large portion of its industrial facilities are losing companies, costing the state significant amounts to cover the deficit in salary discrepancies in self-funded companies. The factories’ lack of attention to occupational safety conditions has increased work risks and fear of working in some industries due to their danger. Additionally, industries face difficulty marketing their products due to import competition and the lack of government support through protecting local products and encouraging their local marketing. Inefficient transportation methods, lack of flexibility, and diversity have made it difficult to transport raw materials and final products between peripheral areas and the city of Baghdad. Regarding industrial pollution, often accompanying spontaneous and unplanned industrial growth, numerous problems affecting the environment arise, including health problems resulting from industrial pollutants. The selection of industrial sites should consider environmental and climatic determinants in industrial localization within the spatial zone. Failure to address these challenges generally leads to industrial growth weakening and declining, which is not in line with the promising future vision of industries in peripheral areas as industrial attraction zones and economic hubs for industrial clustering and transfer from the centre of Baghdad towards Al-Karkh and Al-Rusafa, according to the proposals of the Comprehensive Development Plan for the city of Baghdad for the year 2030, Conclusions and Recommendations, The economic activity in general and the industry in particular face many problems, including changes in demand for production in terms of quantity and type, the issue of raw materials, marketing, workforce, the weakness of financial resources (capital), and the inability to compete with foreign products. Most of its establishments have ceased operations due to the industrial sector’s instability and stagnation resulting from the political instability in the country since 2003. This has led to the absence of a suitable investment environment, as industrial establishments in peripheral areas suffer from the obsolescence of production lines, their primitiveness, the lack of appropriate storage methods, the low skill level of the workforce, in addition to problems with infrastructure, its inefficiency, and power outages, as electricity plays a crucial role in operating production lines regularly. Therefore, there is a need to increase government financial support for the industrial sector by increasing annual financial allocations, considering the position that the Ministry of Industry and the industrial sector are supposed to occupy within the economic system in Iraq, especially with the presence of a number of companies and facilities under this ministry that require qualification and special support for development and achieving the expected and desired role.